2021
DOI: 10.3390/children8040253
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Neonatal Necrotizing Enterocolitis Based on Feeding Practices

Abstract: (1) Background: The relationship between enteral nutrition and neonatal necrotizing enterocolitis (NEC) among premature neonates is still unclear. The present work was designed to assess the relationship between NEC and feeding strategies compared to control infants. (2) Methods: A retrospective case-control study of premature infants (<35 weeks’ gestation) with or without NEC that examined feeding practices and clinical characteristics at birth and 3, 7, and 14-day hospitalization, with a longitudinal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…Studies have shown a significant association between birth weight and risk of development of NEC. 17,18 Even in our study, the birth weight was lower in children who developed NEC (mean birth weight -1193 vs 1162 gms); however the difference was not statistically significant. 5-minute Apgar scores of <7 is was reported as a significant factor for the development of NEC, 17,19 however none of the cases in the current study had lower APGAR score or other features of perinatal asphyxia.…”
Section: Discussioncontrasting
confidence: 68%
“…Studies have shown a significant association between birth weight and risk of development of NEC. 17,18 Even in our study, the birth weight was lower in children who developed NEC (mean birth weight -1193 vs 1162 gms); however the difference was not statistically significant. 5-minute Apgar scores of <7 is was reported as a significant factor for the development of NEC, 17,19 however none of the cases in the current study had lower APGAR score or other features of perinatal asphyxia.…”
Section: Discussioncontrasting
confidence: 68%
“…There is evidence that low birth weight increases the morbidity and mortality of neonates with NEC, 27–29 Sweden, 30 recent advance evidence, 31 systemic review evidence, 32 , 33 Seoul National University Bundang Hospital, Seongnam, Korea, 24 Mexico. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Around 50% of growth in very premature infants (VPI) is estimated to depend on nutritional support [2]. Following an initial period of parenteral nutrition, enteral feeding is provided as milk, with Mother´s Own Milk (MOM) as the best option [3], due to its strong association with a reduction in the incidence of some prematurity-related diseases (such as necrotizing entercolitis), and with a more favourable neurodevelopmental outcome [4][5][6] both of which might be related to an array of bioactive factors [7]. The last published guidance for enteral nutrition in preterm infants by the European Society of Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) [8] recommends an intake of 110-135 kcal/kg/day with between 3.5 and 4.0 (for patients weighing 1000-1800 g) and 4.0-4.5 g/kg/day (if under 1000 g) of protein.…”
Section: Introductionmentioning
confidence: 99%